Drying kinetics and quality of natural coffee - Isquierdo, E. P.; Borem, F. M.; Andrade, E. T. de; Correa, J. L. G.; Oliveira, P. D. de [UNESP]; Alves, G. E. (Amer Soc Agricultural & Biological Engineers, 2013)
The effects of three dry bulb temperatures (35°C, 40°C, and 45°C) and three dew point temperatures (2.6°C, 10.8°C, and 16.2°C) of the drying air on the drying kinetics and sensory quality of natural coffee were evaluated. It was observed that the quality of the coffee beverage depends on the characteristics of the drying air, especially the interaction between the dry bulb temperature values and the dew point. When drying at a dry bulb temperature of 35°C, the beverage quality decreased as the dew point temperature decreased, which represents an increase in the drying rate. However, when drying at a dry bulb temperature of 45°C, the quality of the beverage was reduced both at 2.6°C and 16.2°C dew point temperature. Increasing the dry bulb temperature and decreasing the dew point temperature increased the effective diffusivity coefficient and drying rate and reduced the drying time. Seven mathematical models were fitted to the experimental data to characterize the thin-layer drying of coffee fruits. The modified Midilli and successive residues (with two terms) models were found to best describe the drying process. © 2013 American Society of Agricultural and Biological Engineers.
Keywords: Dry bulb temperature; Dew point temperature; Sensorial analysis; Mathematical models; Drying time; Relative humidity